Innovative approaches in teaching English writing to Chinese speakers - Reynolds, Barry Lee; Teng, Mark Feng (Trends in applied linguistics, 2021)
English writing is acknowledged as an essential skill for critical thinking, learning, and expression, and most EFL learners find themselves struggling when writing in English due to a lack of writing skills, content knowledge, writing strategies, intrinsic motivation, and fluency development practice. This edited volume, covering innovative approaches such as e-learning, strategy-based instruction, metacognitive training, a minimal grammar approach, writing assessment, and a genre-based approach, aims to innovate writing instruction in Chinese speaking regions, which has traditionally been characterized by rigid, teacher-centered, test-oriented approaches. We aim for this edited volume to provide theoretical underpinnings as well as contemporary practical advice related to EFL writing instruction for Chinese speakers